Peran Musyawarah Guru Mata Pelajaran (MGMP) Pendidikan Agama Islam Terhadap Kompetensi Pedagogik Guru di Kota Palembang - Yuni Nopita Sari; Yulia Tri Samiha (Program Magister Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2020)
The purpose of this research is to find out the role ofMGMP PAI SMP Kota Palembang in the design, implementation, and evaluation of learning. This research uses qualitative and quantitative descriptive research methods, conducted at the MGMP secretariat PAI SMP City of Palembang where the research is from March 2019 to July 2019. The subject of this study is all the managers and members of the MGMP PAI SMP City of Palembang. Data collection in this study using observations, interviews, documentation and questionnaire. The analytical techniques used are interactive analysis techniques using data reduction, data presentation, conclusion extraction and using standard deviation techniques. The results show that the role of MGMP PAI SMP Kota Palembang in teacher pedagogical competence is 4: In planning role: (a) role as mediator sharing, mediator discussion mediator enhance teacher competence as a tool to help share, discuss and enhance competency through training, training and workshops, (b) as a facilitator providing services in improving pedagogical competencies of teachers. In performing the role: (a) acting as a reformer in the class room as an innovator in enhancing teacher pedagogical competencies by making interesting learning innovations, (b) acting as an evaluator in the implementation of teaching assessing the performance of learning, whereas in evaluating learning outcomes act as (a) evaluator in the assessment to gauge the effectiveness of the use of assessment tools used by each PAI teacher in the teaching process in school. For MGMP PAI City Palembang's impact on teacher pedagogical competence is for the high category of 38%, while for the category is 38% and for the low category of 24%.